Teacher development in a community of practice in southern Brazil - Kirsch, William (2017)
This dissertation study explored the practices that foster teacher development in a community of practice (Wenger, 1998, 2010) of teachers of English as an Additional Language in a large federal university in the south of Brazil. The community is part of a big internationalization effort in Brazilian universities, named Languages without Borders (LwB). In summary, the goal of the program is to teach additional languages for university students, faculty and staff. For that, the local LwB center has fifteen student teachers, from sophomore to senior year, who are pursuing a teaching certification in English as an Additional Language. Although the community has teaching as its end goal, and not teacher development, teacher development has emerged as an epiphenomenon, for student teachers need to learn how to teach in order for the community’s goals to be attained. The objective of this study was to observe, describe and analyze the practices that foster professional development for these student teachers in order to understand in what ways (and if) the experiences in their everyday life of the community become professional learning. While previous research has shown that communities of practice (Lave & Wenger, 1991; Wenger, 1998) can be sites of learning, and has explored communities among teachers and students in a variety of contexts, there is a scarcity of studies about community among these additional language teachers (Costa, 2013; Merril, 2016) With the theoretical framework of Practice Theory (Wenger, 1998; Young, 2009; Ortner, 1983), this interpretative study (Erickson, 1990) examined history-in-person interviews with focal participants as well as intensive participant observation – recorded in the form of field notes, audio recordings and photographs – and collection of artifacts. The research participants consist of fifteen student teachers, two former student teachers, three Fulbright English Teaching Assistants, and two of the three coordinators of the program at this university. Out of these, five student teachers were chosen for the interviews. Results revealed that this community has both formal and informal practices that cultivate teacher development. The formal practices are planned by the coordinator and enacted in weekly pedagogical meetings, and include practices such as microteaching, workshops and lectures. The informal practices emerge from teachers’ everyday interactions in the teachers’ room, and include practices such as sharing materials, requesting help, sharing classroom stories, sharing specialized concepts and literature in the field of AL teaching, and planning classes together. In conclusion, the landscape of practices that student teachers experience throughout their trajectory in the program helps them develop as teachers through the profession (Nóvoa, 1992) and integrate both technical and practical aspects of the job.